Debating Identity: Reflections on Coverage of Dharaharā and Kāṣṭhmaṇḍap Post Gorkha-Earthquake 2015 - Rajopadhyaya, Abhas Dharananda (Bodhi: An Interdisciplinary Journal, 2019)
The 7.8 Mw Gorkhā-earthquake in April 2015, took 8,857 lives, injured 21,952, destroyed 755,549 buildings, 581 heritages and cost an estimated approximate $513.38 billion. Many heritage sites, including those enlisted in the World Heritage Site, were damaged due to this disaster. The fall of Dharaharā, among all cultural-historical sites, was given (un- ) due attention by many national media, owing to high number of deaths and as a popular landmark of the city. This modern elite tower structure was presented as symbol of national unity and of 'rising back'. But there are other important public heritages too - many centuries older than Dharaharā and they too had stories of deaths, of injuries and of survivals, but received a very small space or almost none in the national media. I take an example of Kāṣṭhamaṇḍap that hosted over 54 people during the earthquake. I have used the method of qualitative content analysis to discuss the construction of identity by national media.